PENGARUH BEBAN KERJA TERHADAP KINERJA KARYAWAN PT. â€œQRâ€ PADA MENARA DANG MERDU BANK RIAU KEPRI SYARIAH - Yapentra, Arhipen (Eko dan Bisnis: Riau Economic and Business Review, 2023)
The purpose of this study was to determine the effect of workload on employee performance at PT. "Qr" at the Dang Merdu Tower of Bank Riau Kepri Syariah. The population of this study were 35 employees of PT "QR" who were assigned as Cleaning Service at the Dang Merdu Tower of Bank Riau Kepri Syariah Pekanbaru City. The sample technique in this study used the census method so that there were 35. The research method used in this study was descriptive and quantitative method and then analyzed using simple linear regression method. The results of data processing obtained the average value of the workload variable is 3.41, meaning that the respondent's answer to all workload statements is Agree (GOOD). Based on the results of the regression test, it is known that the t_count > t_table (29.004 > 2.037) and a significance <0.05 (0.000 <0.05), then Ha is accepted. This means that workload has a positive and significant effect on employee performance at PT. "Qr" at the Dang Merdu Tower of Bank Riau Kepri Syariah. The R square value is 0.487, this shows that workload has an influence on employee performance at PT. "Qr" at the Dang Merdu Tower of Bank Riau Kepri Syariah was 48.7% and the remaining 51.7% was influenced by other variables not examined in this study